Sustainable Marketing Strategies and Financial Performance in the Hotel Industry: Does Digital Transformation and Integration Matter? - Akude, Derrick Nukunu; Akuma, John Kwame; Kwaning, Emmanuel Addai; Asiama, Kojo Agyekum; Amoah-Ahinful, Isaac Kwame (International Review of Management and Marketing, 2025)
This study examined the moderating role of digital transformation and integration in the relationship between sustainable marketing strategies and the financial performance of hotels in Ghana measured by cost efficiency, sales growth and financial stability. The underpinning theories pertinent to this topic include: the dynamic capability theory, resource-based theory, and contingency theory. These collectively furnish a robust foundation for contextualizing the research. The methodological framework employed for this investigation encompasses an explanatory design, integrating a quantitative methodology. A cumulative total of 272 questionnaires were duly filled out by patrons of hotels in Ghana. The empirical findings unveiled a statistically significant positive relationship between sustainable marketing strategies as well as cost efficiency, revenue growth, and financial stability respectively. Moreover, the outcomes indicate that digital transformation alongside integration exerts a significant moderating effect on the relationship between sustainable marketing strategies and the financial performance (cost efficiency, revenue growth, and financial stability) of hotels. The implications derived from this research, both practical and theoretical, are meticulously examined, shedding light on potential applications and influences stemming from the findings within the marketing domain. These implications may encompass realms such as sustainable marketing strategies, cost efficiency, revenue growth, financial stability, as well as the role of digital transformation and integration in the stated relationship. This investigation proffers significant insights pertinent to hotel administrators and policymakers, underscoring the criticality of harmonizing digital transformation with sustainable marketing endeavours to enhance financial outcomes effectively.